Radioactive isotopes measured at Olympic and Paralympic venues in Fukushima Prefecture and Tokyo, Japan - Kaltofen, M. P. J.; Gundersen, A.; Gundersen, M. (Environmental Engineering Science, 2020)
This study detected modest radioactive contamination at Olympic venues in Japan, and found significant alpha-, beta-, and gamma-emitter contamination at Japan's National Training Center. A total of 146 independent soil and dust samples were collected from sites in Fukushima Prefecture, Greater Tokyo, and the heavily traveled corridors between these northern Japan locations to assess radiological contamination related to the Fukushima meltdowns. Thirty-six samples were collected from 2020 Olympic/Paralympic venues, including Yoyogi National Stadium, Shiokaze Park, Olympic Village, Imperial Palace Gardens (all in Tokyo), Azuma Stadium in Fukushima, and the J-Village Olympic and Paralympic National Training Center. Samples were analyzed for beta activity and alpha activity per unit area (Bq/cm2), supplemented by gamma and alpha spectroscopy, with scanning electron microscopy/energy-dispersive X-ray analysis. Mean beta activity was two orders of magnitude greater than mean alpha activity, 459?±?36 net Becquerel per square meter (Bq/m2) versus 5.20?±?2.00 Bq/m2, respectively. Alpha and beta activities were not correlated, with a Pearson product moment correlation coefficient (RSQ) of 0.063. Greater Tokyo Olympic venues showed activities similar to those in the USA control set. In contrast to the Tokyo venues, the mean beta activity for J-Village Training Center samples was 2.4 times higher than for the Greater Tokyo samples. Azuma Park, the Fukushima Baseball venue, was 1.6 times higher than Greater Tokyo venues. The overall Northern Japan sample set displayed an average of 7.0 times greater beta activity than the Tokyo Olympic venues, evidencing the relative success of remediation at Olympic/Paralympic venues compared with other parts of Japan.